Non-support from the immediate boss is associated with stress and unsafety at work - Iredahl, Fredrik; Theodorsson, Elvar; Jones, Mike; Faresjö, Tomas; Faresjö, Åshild (Frontiers in Public Health, 2025)
BackgroundWork-related complaints are often caused by stress and increased mental strain. Support from your immediate boss and colleagues is crucial to buffer against the negative health effects of the psychosocial working environment.AimThe aim of this study was to investigate if support from the immediate boss and colleagues was associated with biological stress levels, unsafety at work, and other work-related conditions.MethodsData derives from a subsample of the SCAPIS study, a major Swedish prospective population-based study. In this subsample, a total of N = 5 058 middle-aged persons (50-64 years) from the general population participated; of these, 68.4% (N = 3 462 individuals) provided hair samples. Questionnaires included socio-demographic and self-reports of occupation, stress, and health status. The demand and control questionnaires were used. A biomarker of long-term stress, hair cortisol concentrations (HCC), was also applied.ResultsIn this studied cohort, 9.1 % reported a lack of support from their immediate boss, while 90.9% reported that they did get support at work. Significantly more women (p < 0.001) reported non-support. Those with support or not did not differ in terms of age, education, civil status, smoking, or ethnicity. Those with non-support reported a higher extent (p < 0.001) of lower perceived health. The risk for hypertension and high cholesterol was increased by 28 %, respectively, 13 % being in the non-support group. The main findings were associations between lack of support and feelings of unsafety at work (p < 0.001), higher long-term cortisol levels (p < 0.009), lack of support from colleagues (p < 0.001), and feelings of dejected/sad (p < 0.001) and high work pace (p = 0.03).ConclusionIndividuals who did not have the necessary support from their immediate boss and colleagues reported they felt more insecure at work and had higher biological long-term stress. In workplace health promotion, an awareness of the link between social support at work and health could be an important component.